Environmental implications of higher ethanol production and use in the U.S.: A literature review. Part I – Impacts on water, soil, and air quality - Hoekman, S. Kent; Broch, Amber; Liu, Xiaowei (Vivian) (Renewable & sustainable energy reviews, 2018)
To address issues of energy security and greenhouse gas (GHG) mitigation, substantial amounts of corn-derived ethanol are used in U.S. gasoline. Currently, ethanol comprises 10% of the U.S. gasoline pool (E10), but there is interest in increasing this – possibly doubling the amount currently used. Production of corn ethanol raises several concerns with respect to environmental and ecological impacts. This paper reviews the available literature regarding the impacts on water, soil, and air quality. A companion paper addresses issues of biodiversity, ecosystems, land use change, greenhouse gas (GHG) emissions, and sustainability. We emphasize recent information appearing since comprehensive reports on this topic were issued by the U.S. EPA and NRC/NAS in 2011. The principal environmental concerns arise from the intensive agricultural activities associated with corn cropping. Nutrient runoff contributes to eutrophication, algal growth, and hypoxia in downstream water bodies; in addition to elevated nitrate pollutant levels in drinking water sources. Water requirements of corn ethanol vary by over 2-orders of magnitude among corn-growing states, depending upon the amount of irrigation used. Significant increases in corn production would likely involve expansion into areas requiring more intensive irrigation. Expansion into Conservation Reserve Program (CRP) lands raises concerns about increased erosion, deterioration of soil quality, loss of biodiversity, and reduction of ecosystem services. Largely because of energy-intensive agricultural activities (including fertilizer production), upstream emissions of most air pollutants of concern are considerably higher for corn ethanol compared to gasoline. Current fuel ethanol levels do not provide any benefit with respect to ground level ozone, and this is unlikely to change with use of E20. However, externalities associated with life-cycle emissions (such as eutrophication, acidification, health effects, etc.) are greater – and more costly – for corn ethanol compared to gasoline. Such externalities are expected to worsen in moving from E10 to E20 fuels.